Kepemimpinan Demokratis Kepala Sekolah dalam Pemanfaatan Ruang GTK untuk Mengembangkan Profesionalisme Guru SD Langensari 03: The Principal's Democratic Leadership in Utilizing the Staff and Teacher Room to Develop the Professionalism of Teachers at SD Langensari 03 - Rina Ardani; Senowarsito Senowarsito; Rosalina Br Ginting (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study is motivated by the importance of developing teacher professionalism in the digital era through the utilization of "Ruang GTK" as a platform for learning and teacher performance management. School principals play a strategic role in fostering teacher professionalism by employing democratic leadership that emphasizes participation, transparency, and collaboration. This study aims to describe and analyze the principal's democratic leadership in using Ruang GTK to develop teacher professionalism at SD Negeri Langensari 03, West Ungaran. The research focuses on the management functions of planning, organizing, implementation, and controlling. The study employed a qualitative approach with a descriptive research design. The research subjects consisted of the principal and teachers. Data collection techniques included interviews, observation, and documentation. Data analysis utilized an interactive model involving data reduction, data presentation, and conclusion drawing. The results indicate that the principal applies democratic leadership across all management functions. During the planning stage, the principal involves teachers in a participatory manner to formulate programs based on needs analysis and performance evaluations. In the organizing stage, the principal establishes working groups and assigns tasks according to teachers' competencies. During the implementation stage, teachers utilize Ruang GTK features—such as Continuous Learning, Career and Performance, and Learning Inspiration—to enhance their competencies both independently and collaboratively. In the controlling stage, the principal supervises, monitors, and provides continuous feedback. The study concludes that the principal's democratic leadership, facilitated by the use of Ruang GTK, effectively develops teacher professionalism in a systematic, participatory, and sustainable manner.